IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DALAM KEPEMIMPINAN KEPALA SEKOLAH DAN DAMPAKNYA TERHADAP MUTU PENDIDIKAN DI SEKOLAH DASAR (STUDI KASUS DI SDN SERANG 15) - Minkhaermidah, Minkhaermidah; Hayadi, B. Herawan; Fidyana, Euis; Setiabudi, Anton; Mutmainah, Siti (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Total Quality Management (TQM) is a management approach focused on continuous quality improvement through the involvement of all organizational components. In the educational context, school principals play a strategic role in implementing TQM principles to improve educational quality. This study aims to describe the implementation of TQM in school leadership and analyze its impact on educational quality at SDN Serang 15. This study employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing, with data validity ensured through triangulation. The results show that TQM implementation is carried out through participatory quality-based planning, implementation of quality improvement programs such as academic supervision, teacher development, and learning innovation, as well as continuous evaluation for improvement. The impact includes improved teacher performance, enhanced learning quality, and the development of a positive and quality-oriented school culture. Therefore, the implementation of TQM in school leadership significantly contributes to improving educational quality in primary schools.